ANALISIS KADAR LEMAK BIJI HOTONG (Sertica italica (L.) Beauv) DENGAN LAMA WAKTU PENYIMPANAN DI KABUPATEN BURU SELATAN - Christina Namarubessy; Ali Awan (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Hotong seeds are a growing and fertile plant on Buru Island and have been exploited by local people as an alternative source of carbohydrates. However, its utilization is still very simple as a result of not knowing the pattern of utilization in other form. Hotong seeds are the smallest cereal seeds weighing 15.2 kg each. Hotong seeds have the highest nutrient content, diameter hot seeds at the base of the larger than the tip and center. The color of seeds are varied hot yellow, brownish and red. Method: This study was an experimental study using Completely Randomized Design (RAL) with long storage treatment (0, 6, 8, and 12 months). Each treatment was repeated three times. The parameters observed were fat content in hotong seeds. Analysis of fat content using descriptive analysis method. Results: The results showed that the fat content of Hotong seeds of Waelo Village differed in control and on each treatment of storage duration. In the control of low fat content of 3.3591%, fat content increased in storage of 6 months and 8 months that is 3.5491% and 3.7242% and then decreased at 12 months ie 3.9322%, where from each treatment fat content the highest was obtained at 12 months storage treatment. Conclusion: There are different amounts of fat content in Hotong seeds of Waelo Village on the controls as well as on any storage treatment duration.